2016
DOI: 10.3311/ppme.8427
|View full text |Cite
|
Sign up to set email alerts
|

The Evaluation of the Parallel Bond’s Properties in DEM Modeling of Soils

Abstract: In this study we conducted the sensitivity analysis of the parallel bond used in the discrete element method (DEM, 3D) IntroductionIt is important for the developing engineers of tillage machines to get fast and accurate feedback on the functionality and effectiveness of new constructions, because of the evolved market competition and the increasing needs of users. We can reconstruct field measurements by the investigations conducted in simulated environments. To investigate the micro-and macro cracks appe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 13 publications
0
2
0
1
Order By: Relevance
“…𝑃𝐵𝑁 and 𝑃𝐵𝑆, parameters that determine the elasticity of the bond through the cylinder formed between adjacent particles, were bonded at 100 MPa and 0.4, respectively. These parameters were determined to demonstrate required stiffness as reported by Kornél Tamás et al [22]. In addition, the variable 𝑆𝐹𝐴 for the circular cross-sectional area was observed to be 1.5 for necessary stiffness and load transfer for the connection between particles with different radii.…”
Section: Ballasted Track Analysis Modelmentioning
confidence: 88%
“…𝑃𝐵𝑁 and 𝑃𝐵𝑆, parameters that determine the elasticity of the bond through the cylinder formed between adjacent particles, were bonded at 100 MPa and 0.4, respectively. These parameters were determined to demonstrate required stiffness as reported by Kornél Tamás et al [22]. In addition, the variable 𝑆𝐹𝐴 for the circular cross-sectional area was observed to be 1.5 for necessary stiffness and load transfer for the connection between particles with different radii.…”
Section: Ballasted Track Analysis Modelmentioning
confidence: 88%
“…𝐵𝑁 and 𝐵𝑆, parameters that determine the elasticity of the bond through the cylinder formed between adjacent particles, were bonded at 100 𝑀 𝑎 and 0.4, respectively. These parameter were determined to demonstrate required stiffness as reported by Kornél Tamás et al 19 In addition, the variable 𝑆𝐹𝐴 for the circular cross-sectional area was observed to be 1.5 for necessary stiffness and load transfer for the connection between particles with different radii. As shown in Figure 6c, an initial vertical displacement of 0.1 mm occurred between the sleeper bottom surface and the gravel.…”
Section: Ballasted Track Analysis Modelmentioning
confidence: 91%
“…Полученные результаты тягового сопротивления сравнивались с получаемыми аналитическим методом и с реальными испытаниями в почвенном канале. В Рисунок 6 -Моделирование взаимодействия с почвой стрельчатой лапы методом CFD сравнении с работами [18,19] результаты были на 5-10 % менее точными, чем при использовании DEM, но потребовалось на порядок меньше вычислительных ресурсов и времени. По сравнению с DEM настройка и запуск симуляции занимает гораздо меньше времени благодаря среде ANSYS и алгоритмам SPH, поскольку мы можем использовать хорошо известные встроенные модели материалов.…”
Section: Introductionunclassified